Feasibility analysis of bone density evaluation with Hounsfield unit value after fibula flap reconstruction of jaw defect - Yihui Yang; Yifan Kang; Yifan Yang; Mengkun Ding; Xiaofeng Shan; Zhigang Cai (SpringerOpen, 2023)
Abstract Background Implant-supported dentures have become an essential means of restoring occlusal function after jaw reconstruction. Bone mineral density (BMD) may influence the success rate of implant denture restorations. This study aimed to explore whether the Hounsfield unit (HU) value can be used to monitor the changing trend of fibular BMD after jaw reconstruction. Results A total of 54 patients who underwent maxillar/mandibular reconstruction with a fibula flap were included in this study. There was a significant correlation between the HU value and BMD at 1 week, 3 months, and 6 months after surgery, and both were significantly correlated with follow-up time. The difference between each pair of absorption rates (DAR) was less than 10% in 66.7% and 75.9% of patients at 3 and 6 months; however, the DAR was more than 20% in 12% and 13.8% of patients at 3 and 6 months, respectively. Conclusions There is a significant correlation between HU value and BMD. The HU value can be used to roughly reflect the fibular BMD changing trend in a group of patients as opposed to an individual, and the HU value is not equivalent to BMD. Trial registration ChiCTR, ChiCTR2300069661, retrospectively registered on 22 March 2023. Retrospectively registered, https://www.chictr.org.cn/showproj.html?proj=188953 .